16. HEALTH STAFF'S WORKING MOTIVATION AT HAI BA TRUNG DISTRICT HEALTH CENTER, HA NOI CAPITAL IN 2022 (Vietnam Journal of Community Medicine, 2023)
Background: Motivation is the factors that motivate each individual to try and strive to perform thetasks to achieve the goals. For medical facilities, the working motivation of medical staff affects thequality of medical service delivery.Objective: Describe working motivation of health workers at Hai Ba Trung District Health CenterHanoi Capital, in 2022.Methods: Cross-sectional study, quantitative research.Results: From the analisis of quantitative information from 339 health workers at Hai Ba TrungDistrict Health Center through questionnaires, the research results show that working motivation ofhealth workers at Hai Ba Trung District Health Center is high (76,8%). Four groups of motivatingfactors have a high percentage of motivated health workers from 71.7% to 80.5%. Four groups ofmaintenance factors have a high percentage of motivated health workers from 67.0% to 80.8%.
Keywords: Working motivation; health workers.